O niilismo e a sua superação para uma transvaloração dos valores em Friedrich Nietzsche - Fernandes, Mateus da Silva (2021)
Abstract: This dissertation examines the Nietzschean thesis of the overcoming of nihilism as a stage in the process of affirmation of life, as a result of his refusal of the nihilist denial of values and his proposal of their overcoming. In this process, we are going to examine Nietzsche's response to the problem of the possibility of nihilism as being, not only a symptom of the weakening of the power without which this overcoming is not possible, but also as a part of this process, that is, as the affirmation, at the same time, of art through the will to power. The scope of this analysis is set by Nietzsche within the field of culture and morals in the Western World. In order to answer this question, we will resort to texts published by Nietzsche during his life, as well as to his posthumous fragments, especially those from 1885 to 1889, as well as contributions on Nietzschean thought of philosophers such as Heidegger and Scarlett Marton, among others. The topics to be examined involve a wide range of themes, such as culture, morals, religion, and science, insofar as, by investigating the foundations on which these domains are founded, we outline an itinerary that focus on the deconstruction and constitution of the foundations of Western thought.